A practical approach example to measurement uncertainty: Evaluation of 26 immunoassay parameters - Kurtulmuş, Yusuf; Tan, Rabia; Yilmaz, Mustafa (Biochemia medica, 2022)
IntroductionMeasurement uncertainty is a non-negative parameter that characterizes the distribution of all values appropriate to the measured size and is associated with the measured result. In this study, we aimed to compare the results with various suggestions and produce more qualified results by calculating the measurement uncertainties of the immunoassays like fertility hormones, drug concentration tests, cardiac markers, thyroid function tests and tumour markers. Materials and methodsUncertainty calculation was made in accordance with the top-down approach according to Nordtest guide. The 12-month study of internal and external quality assessment results were used. The parameters of drug concentration tests were performed on the Abbott Architect c8000, other hormones/markers on the i2000 of the same brand. ResultsFactors that increased the measurement uncertainty of a test were due to external quality control data. The calculations showed that 13 of 26 parameters satisfied quality requirements. The highest uncertainty value, with 28% belonged to cancer antigen 19-9 test. The lowest value was calculated for prolactin with 8.3%. Dehydroepiandrosterone sulfate and phenytoin performed poorly in terms of measurement uncertainty, although internal and external quality control assessment results were considered favourable for both. ConclusionIt is recommended that the concept of measurement uncertainty, which plays an important role in the total quality performance of the laboratory, should be followed up by the clinical laboratory experts at certain time intervals and should be increased the awareness of clinicians about the subject.